Foreign direct investment and exchange rate regimes - Matthias Busse; Carsten Hefeker; Signe Nelgen (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2010)
The paper uses a comprehensive data set with bilateral direct investment flows and establishes the influence of the de-facto exchange rate regime for FDI flows. We find a strong and significant effect from fixed rates on bilateral FDI flows in developed economies, but no significant effect for developing countries. There is thus no general and uniform impact of stable exchange rates on FDI. We provide several possible explanations for this difference.
Keywords: F21; F23; O24; 330; Foreign Direct Investment; Multinational Enterprises; Exchanges Rate Regimes